Features of displaying speed and power capabilities of girls aged 10 years with different level of physical development - O.F. Artyushenko; N.І. Zuyenko; A.O. Artyushenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The sizes of increase of indexes of speed and power capabilities are considered for girls ages 10 years with the different level of physical development as a result of the directed pedagogical influences. 64 girls took part in an experiment. It was conducted for 15 trainings employments in every group in the conditions of health camp. Employments were conducted 5 times per week by duration 45-55 minutes and directed on the increase of level of speed-power preparedness. Playing material made over 50% - from general duration of employments. It is well-proven that girls substantially differentiate on the level of indexes of speed and power capabilities. It is shown that as a result of leadthrough of trainings employments on the standard program (identical for all) increase of result in at run on speed for girls differ substantially. Application of the program results in the substantial increase of result from at run on speed for 15 trainings employments.